The Rhetoric of Empathy: Ethical Foundations of Dialogical Communication - Nathaniel Teich (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
Peter Elbow's "Believing Game" can function as an ethical strategy and can be understood in terms of humanistic rhetorical traditions from Martin Buber to Carl Rogers and Michael Polanyi.